Youth entrepreneurship in agribusiness in India - Babu, Suresh Chandra; Yuan Zhou (Syngenta Foundation, 2023)
This report documents a selected set of case studies of young entrepreneurs in agribusiness in India. Using field visits to their operations and online interviews, we document the issues, challenges, constraints, and opportunities that young agribusiness entrepreneurs face and provide insights for improving the enabling environment, institutional arrangements, and individual capacity for successful entrepreneurship in agribusiness in India. Indian policies related to youth entrepreneurship have evolved rapidly over the past decade. It is a recognition that the youth force, particularly in agriculture and allied sectors, is key to the effective inclusiveness and engagement of youth and women in improving the livelihood and long-term transformation of the agriculture sector. Further, given the recent policy reforms and the associated challenges, studying opportunities for youth in the agriculture sector becomes paramount to guiding the policy and program implementation process from the youth entrepreneurial perspective. Indian policymakers operating in the agricultural and rural development sectors recognize youth entrepreneurship as a critical driver for transforming these sectors. Policy and program interventions at the national level reflect this recognition. Recent economic growth in the last two decades in India has also brought the needed preconditions for youth entrepreneurship. Yet the challenges for entering business opportunities for youth in agriculture remain. There are several structural constraints related to access to technology, finance, institutional support, market access, and business mentorship. These challenges are accentuated further by the needed skills and experience relevant for initiating and running businesses, which remain a significant challenge for the youth in rural India.